Bioinsecticidal and Pharmacological Activities of the Essential Oil of Pogostemon cablin Benth Leaves: A Review - Santos, Lizandra Lima; Brandão, Lethicia Barreto; Costa, Anderson Luiz Pena da; Martins, Rosany Lopes; Rodrigues, Alex Bruno Lobato; Lobato, Adriele Alves; Almeida, Sheylla Susan Moreira da Silva de (Pharmacognosy Reviews)
The plant species Pogostemon cablin (Blanco) Benth (Lamiaceae; Synonyms: Patchouli, Oriza) It is an herb widely used around the world. In traditional medicine it is used in the treatment of inflammation, tumors, in the prevention of oxidative states related to aging, and its ioinsecticidal activities are exploited against insects and microorganisms. For this review, publications from the previous ten years collected in PubMed, Web of Science, Springer, and Scopus were examined. Currently, studies report insecticidal activity in its essential oil (EOPC). However, to better understand the ioinsecticidal activity of EOPC, it is necessary to understand its phytochemistry, which is responsible for its therapeutic activities. Thus, this review aims to describe the phytochemical profile of EOPC, ethnopharmacological uses, and some biological activities of EOPC that are described in this article, but with greater emphasis on its bioinsecticide potential.
Keywords: Insecticide; Patchouli; Lamiaceae; Phytochemistry; Medicinal Plant; Phytotherapy